Q: Simplify 2a plus 3a plus 4 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2a + 4b

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

Related questions

a + a + a - 2a = 3a - 2a = a

2a² + 6a

2a + 4b

5a + 11

1

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

What is the solution of -2a plus 3a plus 5b

depends what 'a' =

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).